Laminate

The laminate with a base material, optically anisotropic layer, and alignment film layer addresses light leakage issues in flat panel displays by controlling liquid crystal alignment, improving display quality.

JP2024178356AInactive Publication Date: 2024-12-24SUMITOMO CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024165232
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2013-08-09
Filing Date
2024-09-24
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional optical films in flat panel display devices suffer from significant light leakage when viewed from an angle during black display.

Method used

A laminate comprising a base material and an optically anisotropic layer with specific refractive index relationships and a polymerizable liquid crystal compound, along with an alignment film layer, is designed to minimize light leakage by controlling the alignment of liquid crystals.

Benefits of technology

The laminate effectively suppresses light leakage during black display, enhancing the viewing experience by maintaining optimal optical properties and reducing noise in display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178356000001_ABST
    Figure 2024178356000001_ABST
Patent Text Reader

Abstract

To provide a laminate for obtaining an optical film excellent in light leakage control as of when viewed from an oblique direction during black display.SOLUTION: A laminate includes a base material and an optically anisotropic layer satisfying the following formulae (1), (2) and (3): Δ50(450) / Δ50(550)≤1.00 (1), 1.00≤Δn50(650) / Δn50 (550) (2) (where, Δn50 (450), Δn50 (550) and Δn50 (650)) are birefringences derived from retardation values obtained by measuring the laminate at wavelengths of 450 nm, 550 nm and 650 nm in a state of inclining a fast axis of the layer at an angle of 50 degrees to act as an inclined central axis; and nz>nx≒ny (3) (where, nx and ny represent respective refractive indexes in directions parallel to a plane of the base material, nx and ny are orthogonal to each other, and nz represents a refractive index in a direction orthogonal to both nx and ny.)SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate. [Background technology]

[0002] Flat panel displays (FPDs) contain optical films such as polarizing plates and retardation plates. As such optical films, polymerizable liquid crystal compounds, photopolymerization initiators, etc. are used. It is known that the coating composition is produced by applying a composition containing an agent and a solvent onto a substrate. For example, Patent Document 1 discloses a method for applying a composition containing a polymerizable liquid crystal compound onto a substrate and vertically aligning the liquid crystal compound. An optical film obtained by mixing and polymerizing the resulting mixture is described. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2006-342332 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, conventional optical films do not adequately suppress light leakage when viewed obliquely during black display. There wasn't. [Means for solving the problem]

[0005] The present invention includes the following inventions. [1] A substrate and an optically anisotropic layer, the optically anisotropic layer being represented by the following formulas (1), (2) and (3): ) A laminate satisfying the above requirements. Δn 50 (450) / Δn 50 (550)≦1.00 (1) 1.00≦Δn 50 (650) / Δn 50(550) (2) (Here, Δn 50 (450), Δn 50 (550), Δn 50 (650) is a wave At lengths of 450 nm, 550 nm, and 650 nm, the fast axis is inclined by 50 degrees. The birefringence is derived from the retardation value obtained when the film is subjected to the measurement. nz>nx≒ny (3) (nx and ny are the refractive indices parallel to the substrate plane, and nx and ny are nz indicates the refractive index in a direction perpendicular to both nx and ny.) [2] The optically anisotropic layer is formed from a composition containing a polymerizable liquid crystal compound and a photopolymerization initiator. The laminate according to [1]. [3] An alignment layer is provided between the substrate and the optically anisotropic layer, and the alignment layer is made of polyimide, polyamide, [1] or [2], which contains at least one selected from the group consisting of amides and polyamic acids. A laminate of. [4] The stacked structure according to [3], wherein the alignment film layer has an alignment control force for vertically aligning the polymerizable liquid crystal compound. Layered body. [5] A polarizing plate (A), the laminate according to any one of [1] to [4], and a polarizing plate (B) laminated in this order. In the above-mentioned configuration, the absorption axes of the polarizing plate (A) and the polarizing plate (B) are perpendicular to each other, and the following (a) and In either case, light is incident from the polarizing plate (B) side and transmitted from the polarizing plate (A) side. The transmittance T at a wavelength of 550 nm obtained when detecting effusion light satisfies the following formula (D): The laminate according to any one of [1] to [4]. (a) When the slow axis exists in the plane of the substrate constituting the laminate, the substrate is disposed on the polarizing plate (B) side. The slow axis of the substrate is arranged parallel to the absorption axis of the polarizing plate (B). (b) When the slow axis does not exist within the plane of the substrate constituting the laminate, the substrate is disposed on the polarizing plate (B) side. Place. 0.000< T <0.005 (D) (Here, transmittance T is the transmittance when the absorption axes of polarizing plate (A) and polarizing plate (B) are arranged parallel to each other.) (This is the value when the pass rate is 100%) [6] The laminate according to any one of [1] to [5], wherein the substrate satisfies the following formula (4): nx>ny≒nz (4) (Here, nx and ny indicate the refractive index in the direction parallel to the substrate plane, and nx and ny are the refractive indices nz indicates the refractive index in a direction perpendicular to both nx and ny.) [7] The laminate according to any one of [1] to [6], wherein the substrate satisfies the following formulae (5) and (6): Δn(450) / Δn(550)≧1.00 (5) 1.00≧Δn(650) / Δn(550) (6) (Δn(450), Δn(550), and Δn(650) are wavelengths of 450 nm and 550 nm, respectively. The birefringence is derived from the front retardation value when measured at 650 nm and 650 nm. ) [8] The laminate according to any one of [1] to [6], wherein the substrate satisfies the following formulae (7) and (8): Δn(450) / Δn(550)≦1.00 (7) 1.00≦Δn(650) / Δn(550) (8) (Δn(450), Δn(550), Δn(650) have the same meaning as above.) [9] The polymerizable liquid crystal compound according to any one of [2] to [8], wherein the polymerizable liquid crystal compound is a compound represented by formula (A). A laminate of. TIFF2024178356000002.tif3179[In formula (A), X 1 is an oxygen atom, a sulfur atom or -NR 1 - stands for R 1 is a hydrogen atom or a group having 1 to 1 carbon atoms Represents the alkyl group of 4. Y1 represents a monovalent aromatic hydrocarbon group having 6 to 12 carbon atoms which may have a substituent, or It represents a monovalent aromatic heterocyclic group having 3 to 12 carbon atoms which may have a substituent. Q 3 and Q 4 each independently represents a hydrogen atom or a C 1-2 0 monovalent aliphatic hydrocarbon group, alicyclic hydrocarbon group having 3 to 20 carbon atoms, and having a substituent. A monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a halogen atom, a cyano group, a nitro group, -NR 2 R 3 or -SR 2 or Q 3 and Q 4 are combined with each other, and each of these becomes R may form an aromatic ring or an aromatic heterocyclic ring together with the carbon atom to which it is bonded. 2 and R 3 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. D 1 and D. 2 each independently represents a single bond, -C(=O)-O-, or -C(=S)-O- , -CR 4 R 5 -, -CR 4 R 5 -CR 6 R 7 -, -O-CR 4 R 5 -, -CR 4 R 5 - O-CR 6 R 7 -,-CO-O-CR 4 R 5 -, -O-CO-CR 4 R 5 -, -CR 4 R 5 -O-CO-CR 6 R 7 -, -CR 4 R 5 -CO-O-CR6 R 7 -OR-NR 4 -C R 5 R 6 -or-CO-NR 4 - represents. R 4 , R 5 , R 6 and R 7 each independently represents a hydrogen atom, a fluorine atom, or a group having 1 to 10 carbon atoms Represents the alkyl group of 4. G 1 and G 2 each independently represents a divalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, The methylene groups constituting the alicyclic hydrocarbon group are replaced by oxygen atoms, sulfur atoms, or -NH-. The methine group constituting the alicyclic hydrocarbon group may be replaced with a tertiary nitrogen atom. It's fine. L 1 and L 2 each independently represents a monovalent organic group; L 1 and L 2 At least The other is an organic group having a polymerizable group.]

[10] A method for producing a laminate, comprising the steps (a1) and (a2). Step (a1): A step of applying a composition containing a polymerizable liquid crystal compound represented by formula (A) to a substrate. Step (a2): A step of drying the applied composition and curing it by light irradiation.

[11] A method for producing a laminate, comprising the steps (b1), (b2) and (b3). Step (b1): A step of applying an alignment polymer to a substrate to form an alignment film layer. Step (b2): A composition containing a polymerizable liquid crystal compound represented by formula (A) is applied onto the alignment film layer. Cloth making process Step (b3): ​​A step of drying the applied composition and curing it by light irradiation.

[12] A polarizing plate comprising the laminate according to any one of [1] to [9].

[13] A display device comprising the laminate according to any one of [1] to [9].

[14] The optically anisotropic layer of the laminate according to any one of [1] to [5] is transferred via a pressure-sensitive adhesive. A laminate comprising a substrate to which the transfer is applied, a pressure-sensitive adhesive layer, and an optically anisotropic layer is obtained. Manufacturing method.

[15] A transfer substrate and an optically anisotropic layer, wherein the optically anisotropic layer is represented by the following formula (1) or (2): and (3). Δn 50 (450) / Δn 50 (550)≦1.00 (1) 1.00≦Δn 50 (650) / Δn 50 (550) (2) (Here, Δn 50 (450), Δn 50 (550), Δn 50 (650) is a wave At lengths of 450 nm, 550 nm, and 650 nm, the fast axis is inclined by 50 degrees. The birefringence is derived from the retardation value obtained when the film is subjected to the measurement. nz>nx≒ny (3) (nx and ny are the refractive indices parallel to the substrate plane, and nx and ny are nz indicates the refractive index in a direction perpendicular to both nx and ny.) Effect of the Invention

[0006] According to the laminate of the present invention, an optical film excellent in suppressing light leakage when viewed obliquely during black display is obtained. is obtained. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view showing an example of a laminate of the present invention. [Diagram 2] FIG. 1 is a cross-sectional schematic diagram illustrating an example of a polarizing plate including a laminate of the present invention. [Diagram 3]FIG. 1 is a cross-sectional view showing an example of a liquid crystal display device including a laminate of the present invention. [Figure 4] FIG. 1 is a cross-sectional view illustrating an example of an organic EL display device including a laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will now be described with reference to the drawings.

[0009] The present invention provides a method for producing an optically anisotropic layer comprising the steps of: The laminate of the present invention (hereinafter, sometimes referred to as the present laminate) satisfies the above requirements and (3). Each of the optically anisotropic layers preferably has one type of optically anisotropic layer having the same composition and optical properties. Δn 50 (450) / Δn 50 (550)≦1.00 (1) 1.00≦Δn 50 (650) / Δn 50 (550) (2) (Here, Δn 50 (450), Δn 50 (550), Δn 50 (650) is a wave At lengths of 450 nm, 550 nm, and 650 nm, the fast axis is inclined by 50 degrees. The birefringence is derived from the retardation value obtained when the film is subjected to the measurement. nz>nx≒ny (3) (nx and ny are the refractive indices parallel to the substrate plane, and nx and ny are nz indicates the refractive index in a direction perpendicular to both nx and ny.)

[0010] A transparent substrate is usually used as the substrate. A transparent substrate is a substrate that is capable of transmitting light, particularly visible light. The term "transparent" refers to a substrate having a translucency that allows the substrate to be transparent to light having a wavelength of 380 to 780 nm. The characteristic of a transparent substrate is that the transmittance is 80% or more. Specific examples of transparent substrates include glass and A light-transmitting resin substrate is exemplified, and a light-transmitting resin substrate is preferred. The substrate is usually a film-shaped substrate. A roll-type film is preferably used.

[0011] The resins that make up the base material are polyethylene, polypropylene, and norbornene-based polymers. Polyolefins such as polyvinyl alcohol; polyethylene terephthalate; polymethacrylate Acrylic acid ester; Polyacrylic acid ester; Cellulose ester; Polyethylene naphtha Polycarbonate; Polysulfone; Polyethersulfone; Polyetherketone Polyphenylene sulfide; and polyphenylene oxide. Polyolefin-based polymers such as polyethylene, polypropylene, and norbornene-based polymers Material is preferred.

[0012] The substrate may be subjected to a surface treatment. The surface treatment may be performed, for example, by vacuum or A method for treating the surface of a substrate with corona or plasma under atmospheric pressure, and a method for treating the surface of a substrate with laser a method for subjecting a substrate surface to ozone treatment, a method for subjecting a substrate surface to saponification treatment, or A method of flame treating the surface, a method of applying a coupling agent to the surface of the base material, or a method of applying a primer The method is to attach reactive monomers or reactive polymers to the surface of a substrate, and then to apply radiation, plasma, etc. and graft polymerization, which involves the reaction by exposure to plasma or ultraviolet light. A method in which the surface of the substrate is subjected to a corona or plasma treatment in air or at atmospheric pressure is preferred.

[0013] The method of treating the surface of a substrate with corona or plasma is as follows: The substrate is placed between the opposing electrodes, and corona or plasma is generated to perform surface treatment on the substrate. A method of plasma generation in which gas is passed between opposing electrodes, and the gas is converted into plasma between the electrodes. A method of spraying a gas onto a substrate, and generating a glow discharge plasma under low pressure conditions, One example is a method of subjecting the substrate to a surface treatment.

[0014] Among these, a substrate is placed between opposing electrodes under pressure close to atmospheric pressure, and corona or plasma is applied to the substrate. A method of generating a gas to perform surface treatment on a substrate, or a method of passing a gas between opposing electrodes to generate a gas to perform surface treatment on a substrate. A preferred method is to convert the gas into plasma between the electrodes and spray the plasma gas onto the substrate. The corona or plasma surface treatment is typically carried out using commercially available surface treatment equipment.

[0015] The optically anisotropic layer in the laminate of the present invention satisfies the following formulae (1), (2) and (3). Δn 50 (450) / Δn 50 (550)≦1.00 (1) 1.00≦Δn 50 (650) / Δn 50 (550) (2) (Here, Δn 50 (450), Δn 50 (550), Δn 50 (650) is a wave At lengths of 450 nm, 550 nm, and 650 nm, the fast axis is inclined by 50 degrees. The birefringence is derived from the retardation value obtained when the film is subjected to the measurement. nz>nx≒ny (3) (nx and ny are the refractive indices parallel to the substrate plane, and nx and ny are nz indicates the refractive index in a direction perpendicular to both nx and ny.)

[0016] Equations (1) and (2) represent the wavelength dispersion in the thickness direction (z direction) of the optically anisotropic layer. Taste. Δn 50 (λ) is the angle at which the optically anisotropic layer is inclined by 50 degrees with the fast axis as the central axis of inclination. , the retardation value R obtained when measured at a wavelength of λ nm 50 (λ) and the thickness of the optically anisotropic layer It can be calculated from d using the following formula (z-1). Δn 50 (λ) = R 50 (λ) / d(z-1) Satisfying formulas (1) and (2) indicates reverse wavelength dispersion, in which the birefringence increases with wavelength. Formula (3) indicates that the optically anisotropic layer has the properties of a positive C plate.

[0017] The optically anisotropic layer is usually a coating layer obtained by applying a solution and drying it. The solution is a composition containing a polymerizable liquid crystal compound and a photopolymerization initiator (hereinafter referred to as an optically anisotropic liquid crystal composition). (sometimes referred to as a layer-forming composition).

[0018] The polymerizable liquid crystal compound may be, for example, a compound represented by formula (A) (hereinafter, “compound (A)”). The polymerizable liquid crystal compound may be of one type or of different structures. A combination of two or more of the above compounds may be used. Compound (A) is a compound described in JP-A-2011-207765. Specifically, the compound represented by formula (A): TIFF2024178356000003.tif3179[In formula (A), X 1 is an oxygen atom, a sulfur atom or -NR 1 - represents. R 1 is a hydrogen atom or carbon Represents an alkyl group having a number of 1 to 4. Y 1is a monovalent aromatic hydrocarbon group having 6 to 12 carbon atoms which may have a substituent or It represents a monovalent aromatic heterocyclic group having 3 to 12 carbon atoms which may have a substituent. Q 3 and Q 4 each independently represents a hydrogen atom or a C 1- 20 monovalent aliphatic hydrocarbon groups, monovalent alicyclic hydrocarbon groups having 3 to 20 carbon atoms, A monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, which may be substituted, a halogen atom, a cyano group, Toro group, -NR 2 R 3 or -SR 2 or Q 3 and Q 4 and are bonded to each other Together with the carbon atom to which they are attached, they form an aromatic ring or an aromatic heterocycle. 2 Oh BiR 3 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. D 1 and D. 2 are each independently a single bond, -C(=O)-O-, -C(=S)-O -, -CR 4 R 5 -, -CR 4 R 5 -CR 6 R 7 -, -O-CR 4 R 5 -, -CR 4 R 5 -O-CR 6 R 7 -,-CO-O-CR 4 R 5 -, -O-CO-CR 4 R 5 -, -CR 4 R 5 -O-CO-CR 6 R 7 -, -CR 4 R 5 -CO-O-CR6 R 7 -OR-NR 4 -CR 5 R 6 -or-CO-NR 4 - represents. R 4 , R 5 , R 6 and R 7 each independently represents a hydrogen atom, a fluorine atom, or a carbon number Represents an alkyl group having 1 to 4 radicals. G 1 and G 2 each independently represents a divalent alicyclic hydrocarbon group having 5 to 8 carbon atoms; The methylene group constituting the alicyclic hydrocarbon group is substituted with an oxygen atom, a sulfur atom or -NH-. The methine group constituting the alicyclic hydrocarbon group may be substituted with a tertiary nitrogen atom. It may be replaced. L 1 and L 2 each independently represents a monovalent organic group; L 1 and L 2 Of At least one of them has a polymerizable group.] Also included are compounds represented by the formula: 1 is a group represented by formula (A1), and L 2 The formula ( Compounds represented by formula (A) in which the group represented by A2) is preferred. P 1 -F 1 -(B 1 -A 1 ) k -E 1 - (A1) P 2 -F 2 -(B 2 -A 2 ) l -E 2 - (A2) [In formula (A1) and formula (A2), B 1 , B 2 , E 1and E 2 are each independently -CR 4 R 5 -, -CH2-CH2 -, -O-, -S-, -CO-O-, -O-CO-O-, -CS-O-, -O-CS-O -, -CO-NR 1 Represents -, -O-CH2-, -S-CH2- or a single bond.

[0019] A 1 and A 2 each independently represents a divalent alicyclic hydrocarbon group having 5 to 8 carbon atoms or A divalent aromatic hydrocarbon group having a prime number of 6 to 18, wherein the methyl groups constituting the alicyclic hydrocarbon group are The aryl group may be replaced by an oxygen atom, a sulfur atom, or -NH-, and the alicyclic hydrocarbon The methine group constituting the group may be replaced by a tertiary nitrogen atom.

[0020] k and l each independently represent an integer of 0 to 3. F 1 and F 2 represents a divalent aliphatic hydrocarbon group having 1 to 12 carbon atoms. P 1 represents a polymerizable group. P 2 represents a hydrogen atom or a polymerizable group. R 4 and R 5 each independently represents a hydrogen atom, a fluorine atom, or an alkoxy group having 1 to 4 carbon atoms; Represents the alkyl group.

[0021] The content of the polymerizable liquid crystal compound in the composition for forming the optically anisotropic layer is It is usually 5 parts by mass to 50 parts by mass, preferably 10 parts by mass, based on 100 parts by mass of the composition. ~30 parts by mass.

[0022] The photopolymerization initiator may be, for example, one that generates radicals upon irradiation with light. Photopolymerization initiators include benzoin compounds, benzophenone compounds, and benzil ketals. Compounds, α-hydroxyketone compounds, α-aminoketone compounds, α-acetophenone compounds Compounds, triazine compounds, iodonium salts and sulfonium salts. Irgacure (registered trademark) 907, 184, 819, and 250 , 369 (all manufactured by BASF Japan Ltd.), Seikuol (registered trademark) BZ , Z, BEE (all manufactured by Seiko Chemical Co., Ltd.), Kayacure (registered Trademark) BP100 (manufactured by Nippon Kayaku Co., Ltd.), UVI-6992 (manufactured by Dow), Adekaop Tomar (registered trademark) SP-152, SP-170 (all manufactured by ADEKA Corporation) , TAZ-A, TAZ-PP (all manufactured by Nippon SiberHegner Co., Ltd.) and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.). Among them, α-acetophenone compounds are preferred. The α-acetophenone compounds include 2-methyl-2-morpholino-1-(4-methylsulfonyl) 2-Dimethylamino-1-(4-morpholino phenyl)-2-benzylbutan-1-one and 2-dimethylamino-1-(4-morpho Examples of the phenyl groups include 2-(4-methylphenyl)-2-(4-methylphenyl)butan-1-one. More preferably, 2-methyl-2-morpholino-1-(4-methylsulfanylphenyl)propionate is used. Propan-1-one and 2-dimethylamino-1-(4-morpholinophenyl)-2-benzo[b]pyrene Commercially available α-acetophenone compounds include dilbutan-1-one. Gacure (registered trademark) 369, 379EG, 907 (all manufactured by BASF Japan Ltd.) and Seikuol (registered trademark) BEE (manufactured by Seiko Chemical Co., Ltd.).

[0023] The photopolymerization initiator is usually used in an amount of 0.1 to 30 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound. The amount of the polymerizable component is preferably 0.5 to 10 parts by mass. The polymerizable liquid crystal compound can be polymerized without disturbing the liquid crystal alignment of the liquid crystal compound.

[0024] The composition for forming an optically anisotropic layer may further contain a polymerization inhibitor, a photosensitizer, a leveling agent, a chiral The adhesive may include a binder, a reactive additive, a solvent, etc.

[0025] [Polymerization inhibitor] The composition for forming the optically anisotropic layer is used to control the polymerization reaction of the polymerizable liquid crystal compound. , a polymerization inhibitor may be contained. Polymerization inhibitors include hydroquinone and alkyl ether-substituted hydrides. Hydroquinones; catechols with alkyl ether or other substituents such as butylcatechol ; Pyrogallols, 2,2,6,6-tetramethyl-1-piperidinyloxy radical, etc. Radical scavengers; thiophenols; β-naphthylamines and β-naphthols Some examples include: The content of the polymerization inhibitor in the composition for forming the optically anisotropic layer is 100% by weight of the polymerizable liquid crystal compound. The amount is usually 0.1 to 30 parts by weight, preferably 0.5 to 10 parts by weight. Within the above range, the polymerizable liquid crystal compound can be polymerized without disturbing the liquid crystal alignment. It is possible.

[0026] [Photosensitizer] Examples of photosensitizers include xanthones such as xanthone and thioxanthone; anthracene and Examples include anthracenes with alkyl ether or other substituents; phenothiazine; and rubrene. Can be obtained. By using a photosensitizer, the photopolymerization initiator can be made highly sensitive. The content is usually 0.1 parts by mass to 30 parts by mass with respect to 100 parts by mass of the polymerizable liquid crystal compound. and preferably 0.5 to 10 parts by mass.

[0027] [Leveling agent] Leveling agents include organic modified silicone oils, polyacrylates, and peracrylates. Fluoroalkyl leveling agents are available. Specifically, DC3PA and SH7PA. , DC11PA, SH28PA, SH29PA, SH30PA, ST80PA, ST86 PA, SH8400, SH8700, FZ2123 (all from Toray Dow Corning ( Co., Ltd.), KP321, KP323, KP324, KP326, KP340, KP341 , X22-161A, KF6001 (all manufactured by Shin-Etsu Chemical Co., Ltd.), TSF400 , TSF401, TSF410, TSF4300, TSF4440, TSF4445, T SF-4446, TSF4452, TSF4460 (all Momentive Performance (manufactured by Mans Materials Japan LLC), Fluorinert (registered trademark) )FC-72, FC-40, FC-43, FC-3283 (all Sumitomo Three (manufactured by M Corporation), Megafac (registered trademark) R-08, R-30, R-90, F- 410, F-411, F-443, F-445, F-470, F-477, F-479, F-482, F-483 (all manufactured by DIC Corporation), F-top (Product name) EF301, EF303, EF351, EF352 (all Mitsubishi) Material Electronics Co., Ltd.), Surflon (registered trademark) S-381, S-382, S-383, S-393, SC-101, SC-105, KH-40, SA-10 0 (all manufactured by AGC Seimi Chemical Co., Ltd.), product names E1830 and E5844 (( Daikin Fine Chemical Research Institute, Ltd.), BM-1000, BM-1100, BYK- 352, BYK-353 and BYK-361N (all trade names: BM Chemie Two or more types of leveling agents may be used in combination.

[0028] By using a leveling agent, a smoother laminated optically anisotropic layer can be formed. In addition, the flowability of the composition for forming the optically anisotropic layer can be controlled during the manufacturing process of the optically anisotropic layer. The content of the leveling agent is, for example, 100 to 200 μm, and the crosslink density of the optically anisotropic layer can be adjusted. The amount is usually 0.1 parts by mass to 30 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound, and is preferably The amount is generally 0.1 to 10 parts by mass.

[0029] [Chiral agent] As the chiral agent, a known chiral agent (for example, the one described in Liquid Crystal Device Handbook, Chapter 3 Section 4-3, Chiral Agents for TN and STN, p. 199, ed., Committee 142 of the Japan Society for the Promotion of Science, 1 989). Chiral agents generally contain an asymmetric carbon atom, but are not axially asymmetric compounds that do not contain an asymmetric carbon atom. Alternatively, planar chiral compounds can be used as chiral agents. Axially chiral compounds or Planar chiral compounds include binaphthyl, helicene, paracyclophane and their derivatives. The body is mentioned. Specifically, see JP 2007-269640 A and JP 2007-269639 A , JP 2007-176870 A, JP 2003-137887 A, JP 200 JP-A-0-515496, JP-A-2007-169178 and JP-T-9-5060 88, and preferably the compounds described in BASF Japan Ltd. ) Paliocolor(R) LC756. The content of the chiral agent is usually 0.1 parts by mass to 100 parts by mass of the polymerizable liquid crystal compound. 30 parts by mass, and preferably 1.0 part by mass to 25 parts by mass. When polymerizing a polymerizable liquid crystal compound, the liquid crystal alignment of the polymerizable liquid crystal compound is further prevented from being disturbed. can.

[0030] [Reactive additives] The reactive additive has a carbon-carbon unsaturated bond and an active hydrogen reactive group in its molecule. The "active hydrogen reactive group" referred to here is preferably a carboxyl group (- For groups with active hydrogen such as COOH, hydroxyl groups (-OH), and amino groups (-NH2) It means a reactive group, such as a glycidyl group, an oxazoline group, a carbodiimide group, an aziridyl group, Substitutes include dimethyl groups, imide groups, isocyanato groups, thioisocyanato groups, and maleic anhydride groups. This is an example table.

[0031] In the reactive additive, it is preferable that at least two active hydrogen reactive groups are present. In this case, the multiple active hydrogen reactive groups present may be the same or different.

[0032] The carbon-carbon unsaturated bond of the reactive additive is a carbon-carbon double bond or a carbon-carbon It may be a carbon-carbon double bond, triple bond, or a combination thereof, but is preferably a carbon-carbon double bond. Among them, the reactive additive is preferably a compound having a vinyl group and / or a (meth)acrylic group. It is preferable that the active hydrogen reactive group contains a carbon-carbon unsaturated bond. At least one selected from the group consisting of a lysidyl group and an isocyanato group is preferred. Of these, reactive additives having an acrylic group and an isocyanato group are particularly preferred.

[0033] Specific examples of reactive additives include methacryloxyglycidyl ether and acryloxyglycidyl ether. Compounds having a (meth)acrylic group and an epoxy group, such as aryl ether; (Meth)acrylic and oxetane groups, such as acrylate and methacrylate Compounds having the formula (meth)acrylate, such as lactone acrylate and lactone methacrylate. Compounds containing acrylic and lactone groups; vinyloxazoline and isopropenyloxazoline. Compounds having a vinyl group and an oxazoline group, such as phosphorus; isocyanatomethyl acrylate acrylate, isocyanatomethyl methacrylate, 2-isocyanatoethyl acrylate and 2 - (meth)acrylic group and isocyanato group, such as isocyanatoethyl methacrylate In addition, methacrylic anhydride, acrylic anhydride, and the like can be used. Vinyl or vinylene groups and acid anhydrides, such as maleic anhydride and vinyl maleic anhydride Among them, methacryloxyglycidyl ether, acryloyloxyglycidyl ether, etc. Aryloxyglycidyl ether, isocyanatomethyl acrylate, isocyanatomethyl methacrylate acrylate, vinyloxazoline, 2-isocyanatoethyl acrylate, 2-isocyanatoethyl acrylate Preferred are isocyanatoethyl methacrylate and its oligomers, and Of these, acrylate, 2-isocyanatoethyl acrylate and oligomers thereof are particularly preferred.

[0034] Here, a more preferred reactive additive having an isocyanato group as the active hydrogen reactive group is The preferred reactive additive is, for example, a reactive additive represented by the following formula (Y): . TIFF2024178356000004.tif1695[In formula (Y), n is an integer from 1 to 10, R 1’ is a divalent aliphatic or alicyclic group having 2 to 20 carbon atoms Each repeating unit represents a hydrocarbon group of the formula: Two R's in the top 10 2’ is -NH- on one side and >NC(=O)-R on the other side. 3’ Shown in R 3’ represents a hydroxyl group or a group having a carbon-carbon unsaturated bond. R in formula (Y) 3’ At least one R 3’ has a carbon-carbon unsaturated bond It is a group.

[0035] Among the reactive additives represented by the formula (Y), the compound represented by the following formula (YY) Hereinafter, sometimes referred to as "compound (YY)" is particularly preferred (n is the number of the preceding (This has the same meaning as above.) TIFF2024178356000005.tif41125 Compound (YY) may be used as is or after purification as necessary. Commercially available products include, for example, Laromer (registered trademark) LR-9000 (manufactured by BASF) ) etc.

[0036] The content of the reactive additive is usually 0.1 parts by mass per 100 parts by mass of the polymerizable liquid crystal compound. The amount is from 0.1 to 5 parts by mass.

[0037] [solvent] The composition for forming the optically anisotropic layer contains a solvent, In particular, it is preferable that the liquid crystal composition contains an organic solvent. The organic solvent is an optically anisotropic liquid crystal compound such as a polymerizable liquid crystal compound. The organic solvent is preferably capable of dissolving the components of the composition for forming the photosensitive layer, and more preferably dissolves the photopolymerizable liquid crystal compound and the like. A solvent capable of dissolving the components of the composition for forming an optically anisotropic layer and a polymerizable liquid crystal compound. More preferred is a solvent that is inactive to the polymerization reaction. Specifically, methanol, ethanol, ethyl acetate, etc. ethylene glycol, isopropyl alcohol, propylene glycol, methyl cellosolve, Alcohols such as butyl cellosolve, propylene glycol monomethyl ether, and phenol Solvents: ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ- Butyrolactone, propylene glycol methyl ether acetate, ethyl lactate, etc. Ether solvents; acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl Ketone solvents such as amyl ketone, methyl isobutyl ketone, etc.; pentane, hexane, hepta non-chlorinated aliphatic hydrocarbon solvents such as toluene and xylene; non-chlorinated aromatic hydrocarbon solvents such as toluene and xylene Agent; nitrile solvent such as acetonitrile; acetone solvent such as tetrahydrofuran, dimethoxyethane terephthalic acid solvents; and chlorinated hydrocarbon solvents such as chloroform and chlorobenzene. Two or more organic solvents may be used in combination. Among them, alcohol solvents, ester solvents, etc. Preferred are solvents, ketone solvents, non-chlorinated aliphatic hydrocarbon solvents and non-chlorinated aromatic hydrocarbon solvents. I wish.

[0038] The composition for forming an optically anisotropic layer may further contain a compound different from the compound (A). stomach.

[0039] As the polymerizable liquid crystal compound different from the compound (A), for example, a compound having a group represented by the formula (X) A compound containing the compound (hereinafter, sometimes referred to as "compound (X)"). may be one type, or a plurality of compounds having different structures may be combined. P 11 -B 11 -E 11 -B 12 -A 11 -B 13 - (X) [In formula (X), P 11 represents a polymerizable group. A 11 represents a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group. The hydrogen atoms contained in the alicyclic hydrocarbon group and the divalent aromatic hydrocarbon group may be replaced by halogen atoms, Substituted with an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cyano group, or a nitro group The alkyl group having 1 to 6 carbon atoms and the alkoxy group having 1 to 6 carbon atoms may be The hydrogen atoms contained therein may be substituted with fluorine atoms. B 11 -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, -CO -NR 16 -, -NR 16 Represents -CO-, -CO-, -CS- or a single bond. R 16 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. B 12 and B. 13 are each independently -C≡C-, -CH=CH-, -CH2-C H2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-N R 16 -, -NR 16 -C(=O)-, -OCH2-, -OCF2-, -CH2O-, - CF2O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH- or Represents a single bond. E 11 represents an alkanediyl group having 1 to 12 carbon atoms, The hydrogen atom may be substituted with an alkoxy group having 1 to 5 carbon atoms. The hydrogen atoms contained therein may be substituted with halogen atoms. In the above formula, -CH2- may be replaced with -O- or -CO-.

[0040] The number of carbon atoms in the divalent aromatic hydrocarbon group and the divalent alicyclic hydrocarbon group represented by A11 is: The range is preferably 3 to 18, more preferably 5 to 12, and even more preferably 5 or less. It is particularly preferred that A is 1 or 6. 11 As an example, cyclohexane-1,4-diyl group , 1,4-phenylene groups are preferred.

[0041] E 11 The alkanediyl group having 1 to 12 carbon atoms represented by the formula (I) is a linear alkanediyl group having 1 to 1 The alkanediyl group having 1 to 12 carbon atoms is preferably an alkanediyl group having -CH 2- may be replaced by -O-. Specifically, methylene group, ethylene group, propane-1,3-diyl group, butane-1,4 -diyl group, pentane-1,5-diyl group, hexane-1,6-diyl group, heptane-1 ,7-diyl group, octane-1,8-diyl group, nonane-1,9-diyl group, decane-1 ,10-diyl, undecane-1,11-diyl and dodecane-1,12-diyl Linear alkanediyl groups having 1 to 12 carbon atoms, such as -CH2-CH2-O-CH2-CH 2-, -CH2-CH2-O-CH2-CH2-O-CH2-CH2- and -CH2- CH2-O-CH2-CH2-O-CH2-CH2-O-CH2-CH2-CH2- and the like. do. B 11 As the alkyl group, -O-, -S-, -CO-O-, and -O-CO- are preferable, and among them, --CO--O-- is more preferred. B 12 and B. 13 Each of the following is independently selected from the group consisting of -O-, -S-, -C(=O)-, - C(=O)-O-, -OC(=O)-, and -OC(=O)-O- are preferred, and among these, --O-- or --OC(.dbd.O)--O-- is more preferred.

[0042] P 11 The polymerizable group represented by the formula (I) is preferably a radical polymerizable group because it is easily photopolymerizable. A group or a cationic polymerizable group is preferred, as it is easy to handle and the polymerizable liquid crystal compound can be produced automatically. Since the polymerization is easy, the polymerizable group is represented by the following formulas (P-11) to (P-15). It is preferable that the group be a group in which TIFF2024178356000006.tif33154 [Formula (P-11) to (P-15), R 17 ~R 21 each independently represents an alkyl group having 1 to 6 carbon atoms or a hydrogen atom. .]

[0043] Specific examples of the groups represented by formulae (P-11) to (P-13) include the groups represented by the following formula (P-16): ) to (P-20). TIFF2024178356000007.tif30131

[0044] P 11 is preferably a group represented by formula (P-14) to formula (P-20), More preferred are a nyl group, a p-stilbene group, an epoxy group or an oxetanyl group. P 11 -B 11 The group represented by - is an acryloyloxy group or a methacryloyloxy group. An oxy group is more preferred.

[0045] Compound (X) may be any of the compounds represented by formula (I), (II), (III), (IV), and (V). Or a compound represented by formula (VI): P 11 -B 11 -E 11 -B 12 -A 11 -B 13 -A 12 -B 14 -A 13 -B 15 -A 14 -B 16 -E 12 -B 17 -P 12 (I) P 11 -B 11 -E 11 -B 12 -A 11 -B 13 -A 12 -B 14 -A 13 -B 15 -A 14 -F 11 (II) P 11 -B 11 -E 11 -B 12 -A 11 -B 13 -A 12 -B 14 -A 13 -B 15 -E 12 -B 17 -P 12 (III) P 11 -B 11 -E 11 -B 12 -A 11 -B13 -A 12 -B 14 -A 13 -F 11 (IV) P 11 -B 11 -E 11 -B 12 -A 11 -B 13 -A 12 -B 14 -E 12 -B 17 -P 12 (V) P 11 -B 11 -E 11 -B 12 -A 11 -B 13 -A 12 -F 11 (VI) (In the formula, A 12 ~A 14 are each independently, A 11 is synonymous with B 14 ~B 16 Each is unique Standing, B 12 is synonymous with B 17 is B 11 is synonymous with E 12 E 11 Synonymous with be. F 11 represents a hydrogen atom, an alkyl group having 1 to 13 carbon atoms, an alkoxy group having 1 to 13 carbon atoms, Cyano group, nitro group, trifluoromethyl group, dimethylamino group, hydroxyl group, methylo Alkyl group, formyl group, sulfo group (-SO3H), carboxy group, and alcohol with 1 to 10 carbon atoms. represents an oxycarbonyl group or a halogen atom, and the alkyl group and alkoxy group are The -CH2- may be replaced by -O-.

[0046] Specific examples of compound (X) include those described in Liquid Crystal Handbook (Liquid Crystal Handbook Editorial Committee, Maruzen Co., Ltd., 1999) "3.8.6 Network (fully cross-linked type)" and "6.5.1 Liquid crystal materials b. Polymerizable nematic liquid crystal materials" that have a polymerizable group. Compounds disclosed in JP 2010-31223 A, JP 2010-270108 A, and JP The polymerizable liquid crystal composition described in JP-A-2011-6360 and JP-A-2011-207765 Examples include compounds.

[0047] Specific examples of the compound (X) include the compounds represented by the following formulae (I-1) to (I-4) and (II-1) to (II-5) Formula (II-4), Formula (III-1) ~ Formula (III-26), Formula (IV-1) ~ Formula (IV- 26), represented by formula (V-1) to formula (V-2) and formula (VI-1) to formula (VI-6) In the following formula, k1 and k2 each independently represent an integer of 2 to 12. These compounds (X) are selected from the group consisting of compounds (X) having ease of synthesis and availability. In this respect, it is preferable.

[0048] TIFF2024178356000008.tif77147

[0049] TIFF2024178356000009.tif77148

[0050] TIFF2024178356000010.tif152149

[0051] TIFF2024178356000011.tif216145

[0052] TIFF2024178356000012.tif124139

[0053] TIFF2024178356000013.tif245140

[0054] TIFF2024178356000014.tif82142

[0055] TIFF2024178356000015.tif11894

[0056] TIFF2024178356000016.tif139123

[0057] By adjusting the mixing amount of the compound (X) and the compound (A), the wavelength resolution of the laminate of the present invention can be improved. The dispersion characteristics can be controlled. The amount is usually 5 to 50 parts by mass based on 100 parts by mass of the composition for forming an optically anisotropic layer. and preferably 5 parts by mass to 10 parts by mass. The content of the compound (X) in the composition for forming an optically anisotropic layer is 100% by mass of the compound (A). The amount of the component (s) is usually 0 to 50 parts, and preferably 0 to 10 parts.

[0058] In order to align the polymerizable liquid crystal compound contained in the optically anisotropic layer, the optically anisotropic layer is formed on a substrate. Although the forming composition may be applied, an alignment film layer may also be used. An alignment layer may be provided between the substrate and the optically anisotropic layer.

[0059] The alignment film layer in the present invention is insoluble in the composition for forming an optically anisotropic layer. The change occurs when the solvent contained in the composition is removed or when the polymerizable liquid crystal compound is heated to adjust its liquid crystal alignment. It is preferable that the laminate does not peel off due to friction or the like during transportation.

[0060] Generally, the method of forming an alignment layer is to apply an alignment polymer to the surface of a substrate and then dry it. a method of applying an orientation polymer, drying the polymer, and rubbing the surface; a method of applying a coating of a fluorine-based fluoride, drying the coating and irradiating the coating with polarized light; a method of depositing silicon oxide by oblique deposition; and Form a monolayer with long-chain alkyl groups using the Muir-Blodgett technique (LB technique). Methods, etc. The alignable polymer and the photoalignable polymer are usually dissolved in a solvent and then applied.

[0061] Oriented polymers include polyamides and gelatins that have amide bonds in the molecule, and Polyimide having imide bonds in its hydrolyzate, polyamic acid, polyvinyl chloride, etc. Alkyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazolamide Polyvinylpyrrolidone, polyacrylic acid, Among them, polyamide, polyimide, etc. The alignment film layer may be formed of one type of alignment polymer. Alternatively, a composition in which a plurality of types of polymers are combined may be used. These polymers may be copolymers obtained by polycondensing monomers by dehydration, dealcoholization, etc. In the case of the above, radical polymerization, anionic polymerization, cationic polymerization, or other chain polymerization, coordination polymerization, ring-opening polymerization, etc. can be easily obtained by Commercially available oriented polymers include SunEver (registered trademark, manufactured by Nissan Chemical Industries, Ltd.), Optomer (registered trademark, manufactured by JSR) and the like. The alignment film layer formed from such an alignment polymer can align the liquid crystal of the polymerizable liquid crystal compound. In addition, depending on the type of alignment polymer and the rubbing conditions, horizontal alignment, vertical alignment, etc. can be achieved. It is possible to control various liquid crystal alignments such as hybrid alignment and tilt alignment, and it is suitable for various liquid crystal panels. This can be used to improve the viewing angle.

[0062] The photo-alignable polymer includes a polymer having a photosensitive structure. When a polymer having the above structure is irradiated with polarized light, the photosensitive structure in the irradiated area is isomerized or crosslinked. This causes the photo-oriented polymer to be oriented, and an orientation control force is imparted to the film made of the photo-oriented polymer. Examples of the photosensitive structure include an azobenzene structure, a maleimide structure, and a chalcone structure. structure, cinnamic acid structure, 1,2-vinylene structure, 1,2-acetylene structure, spiropyran structure, Examples of the structure include a spirobenzopyran structure and a fulgide structure. The polymer may be one type, or a combination of multiple polymers having different structures. The photo-alignable polymer may be a copolymer having a plurality of different photosensitive structures. Monomers with the same structure are polymerized by polycondensation such as dehydration and dealcoholization, radical polymerization, anionic polymerization, It can be obtained by chain polymerization such as cationic polymerization, coordination polymerization, ring-opening polymerization, or the like. Oriented polymers are disclosed in Japanese Patent No. 4450261, Japanese Patent No. 4011652, and Japanese Patent Publication No. 10-49230, Patent No. 4404090, JP 2007-156439 A and photo-alignable polymers described in JP-A-2007-232934. However, as a photo-aligned polymer, from the viewpoint of durability, a cross-linked structure is formed by irradiating polarized light. Preferred are polymers which

[0063] In the present invention, the orientation uniformity of the polymerizable liquid crystal compound and the manufacturing time of the optically anisotropic layer are particularly important. From the viewpoint of production cost, the polymer is selected from polyimide, polyamide, or polyamic acid. Method for applying and drying an oriented polymer made of a material, and method for applying and drying an oriented polymer A method of rubbing the surface of the perilla is preferred.

[0064] Examples of the solvent for dissolving the alignment polymer or the photoalignment polymer include water; alcohol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol , methyl cellosolve, butyl cellosolve and other alcohol solvents; ethyl acetate, butyl acetate, Ethylene glycol methyl ether acetate, gamma-butyrolactone, propylene glycol ethyl ether acetate, ethyl lactate, and other ester solvents; acetone, methyl ethyl Ketones, cyclopentanone, cyclohexanone, methyl amyl ketone, methyl isobutyl Ketones, ketone solvents such as N-methyl-2-pyrrolidone; pentane, hexane, heptane, Aliphatic hydrocarbon solvents such as ethylcyclohexane; toluene, xylene, chlorobenzene, etc. Aromatic hydrocarbon solvents; acetonitrile and other nitrile solvents; propylene glycol monomer solvents Ether solvents such as ethyl ether, tetrahydrofuran, dimethoxyethane, etc.; chloroform These organic solvents may be used alone or in combination. You can also match them.

[0065] The solvent is usually 10 parts by mass per 100 parts by mass of the alignment polymer or photoalignment polymer. The amount of the fluorine-containing compound is preferably from 1,000 to 50,000 parts by mass, and more preferably from 1,000 to 50,000 parts by mass. It is more preferably 2,000 parts by mass to 20,000 parts by mass.

[0066] The method of applying an oriented polymer or a photo-oriented polymer dissolved in a solvent to a substrate is as follows: , extrusion coating method, direct gravure coating method, reverse gravure coating method Coating method, CAP coating method, die coating method, etc. Also, a coating method using a coater such as a brush coater, a bar coater, or a spin coater can be used. can be.

[0067] Drying methods include natural drying, ventilation drying, heat drying, reduced pressure drying, and combinations of these. The drying temperature is preferably 10 to 250°C, more preferably 25 to 200°C. The drying time depends on the type of solvent, but is preferably 5 seconds to 60 minutes, and 10 seconds More preferably, it is for up to 30 minutes.

[0068] The rubbing method is a rotating rubbing roll with a rubbing cloth wrapped around it. with the oriented polymer that has been applied to the substrate and dried.

[0069] The polarized light irradiation method uses the device described in JP-A-2006-323060. Alternatively, a method of forming a pattern in a desired region by applying a photomask corresponding to the region to the desired region may be used. A patterned alignment film layer is formed by repeatedly irradiating each region with polarized light such as linearly polarized ultraviolet light. Photomasks are usually made of quartz glass, soda lime glass or The light-shielding pattern is formed on a polyester film. Areas covered with the shading block the polarized light that is being irradiated, while areas not covered are irradiated. Polarized light is transmitted. Quartz glass is preferred because it is less affected by thermal expansion. In view of the reactivity of the polymer, the polarized light to be irradiated is preferably ultraviolet light.

[0070] The thickness of the alignment film layer is usually 10 nm to 10,000 nm, and preferably 10 nm to 10 00nm. When the thickness of the alignment film layer is within the above range, the polymerizable liquid crystal compound can be easily aligned in a desired direction or angle. This is preferable because it allows crystal orientation.

[0071] The liquid crystal alignment state of the polymerizable liquid crystal compound includes horizontal alignment, vertical alignment, hybrid alignment, and The horizontal, vertical, and other expressions are based on the substrate surface. This refers to the orientation direction of the long axis of the polymerizable liquid crystal compound. For example, vertical alignment is The major axis of the polymerizable liquid crystal compound is in the vertical direction.

[0072] The state of liquid crystal alignment changes depending on the properties of the alignment film layer and the polymerizable liquid crystal compound. For example, the alignment film layer may be used to regulate the alignment of the liquid crystal molecules horizontally. If the material expresses the liquid crystal molecules, the polymerizable liquid crystal compound forms a horizontal alignment or a hybrid alignment. If the polymerizable liquid crystal compound is a material that can exhibit vertical alignment, the polymerizable liquid crystal compound can exhibit vertical alignment or A tilted orientation can be formed. When the alignment film layer is made of an alignment polymer, the alignment control force depends on the surface condition and the rabit. The orientation of the film can be adjusted by changing the application conditions. In the case of the polymerizable liquid crystal, the polarized light irradiation conditions can be adjusted arbitrarily. By selecting the physical properties of the compound, such as surface tension and liquid crystallinity, it is possible to control the liquid crystal alignment. can.

[0073] In the present invention, the alignment film layer has an alignment control force capable of vertically aligning the polymerizable liquid crystal compound. Specifically, it is preferable that the oriented polymer contains silicon atoms, fluorine atoms, etc. For example, Japanese Patent No. 4605016 and Japanese Patent No. 4 985906, Patent No. 4502119 or WO2008 / 117760 The material is generally used as a liquid crystal alignment film for vertical alignment type liquid crystal display elements. Fees can be used.

[0074] The polymerizable liquid crystal compound contained in the applied composition for forming an optically anisotropic layer is in a nematic phase or the like. When the liquid crystal phase is exhibited, it has birefringence due to monodomain alignment. In order to achieve this, a composition for forming an optically anisotropic layer is applied onto a substrate or an alignment film layer, and then light is irradiated. This causes the material to harden.

[0075] The method for applying the composition for forming the optically anisotropic layer onto the substrate or the alignment film layer includes extrusion coating. coating method, direct gravure coating method, reverse gravure coating method, Examples of the coating method include CAP coating method, slit coating method, and die coating method. Alternatively, the coating may be performed using a coater such as a dip coater, a bar coater, or a spin coater. Among them, the C method is the most popular because it can be applied continuously in a roll-to-roll format. AP coating method, inkjet method, dip coating method, slit coating method The roll coating method, die coating method and bar coater coating method are preferred. In the case of applying by roll method, a composition containing an oriented polymer is applied to a substrate to form an oriented film layer. It is also possible to form an optically anisotropic layer on the resulting alignment film layer.

[0076] The light irradiation is usually carried out with visible light, ultraviolet light or laser light, with ultraviolet light being preferred.

[0077] The light irradiation may be performed on the applied composition for forming an optically anisotropic layer as it is. When the layer-forming composition contains a solvent, it is preferable to dry the composition to remove the solvent before irradiating the layer with light. The optically anisotropic layer can be formed by removing the solvent from the applied composition for forming the optically anisotropic layer. The polymerizable liquid crystal compound contained in the layer-forming composition forms liquid crystal alignment. Drying (removal of solvent) The solvent may be removed in parallel with the light irradiation, but most of the solvent should be removed before the light irradiation. As the drying method, the same drying method as that used in forming the alignment film layer can be used. Among them, natural drying or heat drying is preferable. The drying temperature is 0°C to 250°C. The range is preferably 50°C to 220°C, more preferably 60°C to 170°C. The drying time is preferably from 10 seconds to 60 minutes, and more preferably from 30 seconds to It lasts for 30 minutes.

[0078] When the laminate of the present invention is placed between polarizing plates whose absorption axes are perpendicular to each other, light leakage is extremely small. Specifically, in a structure in which a polarizing plate (A), the present laminate, and a polarizing plate (B) are laminated in this order, The absorption axes of the polarizing plate (A) and the polarizing plate (B) are perpendicular to each other, and either (a) or (b) below is satisfied. In either case, light is incident from the polarizing plate (B) side and transmitted light is detected from the polarizing plate (A) side. The transmittance T at a wavelength of 550 nm obtained when the optical fiber is exposed satisfies the following formula (D). (a) When the slow axis exists within the plane of the substrate constituting the laminate, the substrate is placed on the polarizing plate (B) side. In addition, the slow axis of the substrate is laminated in parallel with the absorption axis of the polarizing plate (B). (b) When the slow axis does not exist within the plane of the substrate constituting the laminate, the substrate is arranged on the polarizing plate (B) side. Place it. 0.000< T <0.005 (D) (Here, transmittance T is the transmittance when the absorption axes of polarizing plate (A) and polarizing plate (B) are arranged parallel to each other.) (This is the value when the pass rate is 100%)

[0079] When the slow axis exists in the plane of the substrate (case (a)), the absorption axis of the polarizing plate and the slow axis of the substrate are If the substrates are not parallel, a phase difference will occur, and light leakage will occur only through the substrate. When checking the properties of the laminate, it is necessary to laminate as described above in (a).

[0080] If the slow axis does not exist within the substrate plane (case (b)), how should it be placed between the polarizing plates? Since no phase difference occurs, the characteristics of the laminate can be confirmed.

[0081] The transmittance T at a wavelength of 550 nm expressed by formula (D) is calculated using a general UV-Vis spectrophotometer. The transmittance when the absorption axes of polarizing plate (A) and polarizing plate (B) are arranged parallel to each other is The laminate of the present invention is placed between polarizing plates (A) and (B) whose absorption axes are perpendicular to each other. By inserting it and measuring it, you can check the degree of light leakage. The laminate obtained by the present invention has excellent alignment properties, and therefore, light leakage caused by disturbance in the alignment of the liquid crystal is prevented. This makes it possible to significantly suppress leakage, and the characteristics are also excellent when incorporated into a display device. .

[0082] The substrate in the present invention preferably satisfies the following formula (4). nx>ny≒nz (4) (Here, nx and ny indicate the refractive index in the direction parallel to the substrate plane, and nx and ny are the refractive indices nz indicates the refractive index in a direction perpendicular to both nx and ny.)

[0083] Examples of substrates that satisfy formula (4) include Arton Film (manufactured by JSR Corporation), ZeonoAffinity Rum (Optes Co., Ltd.), S-Cina (Sekisui Chemical Co., Ltd.), VA-TAC (Comic Examples of the antibacterial agent include SUMIKALITE (manufactured by Sumitomo Chemical Co., Ltd.) and SUMIKALITE (manufactured by Sumitomo Chemical Co., Ltd.).

[0084] When the substrate satisfies the relationship nx>ny≒nz, it is generally called a negative B plate. If the optical properties are such that nx>ny=nz, it is called a positive A plate. By using these base materials, the compensation effect of the laminate can be improved. However, it is preferable to use nx>ny≒nz in view of ease of manufacturing the substrate.

[0085] Further, the substrate in the present invention is preferably a compound represented by the following formulas (5) and (6), or the following formula (7): ) and (8). Δn(450) / Δn(550)≧1.00 (5) 1.00≧Δn(650) / Δn(550) (6) Δn(450) / Δn(550)≦1.00 (7) 1.00≦Δn(650) / Δn(550) (8) (Here, Δn(450), Δn(550), and Δn(650) are the wavelengths of 450 nm. Birefringence derived from the front retardation value when measured at 550 nm, 650 nm It is.)

[0086] As the substrate satisfying the formulas (5) and (6), the commercially available Examples of such films include:

[0087] An example of a substrate that satisfies the formulas (7) and (8) is "PureAce (registered trademark) WR ” (Teijin Limited), etc.

[0088] Equations (5) and (6) mean that the longer the wavelength, the smaller the birefringence. Equations (7) and (8) show that the longer the wavelength, the larger the birefringence. This means that the wavelength dispersion of the substrate is reverse wavelength dispersion.

[0089] The present laminate can be produced by a production method including the following steps (a1) and (a2): can. Step (a1): A step of applying a composition containing a polymerizable liquid crystal compound represented by formula (A) to a substrate. Step (a2): A step of drying the applied composition and curing it by light irradiation.

[0090] The laminate can be produced by a production method including the following steps (b1), (b2) and (b3): It can be manufactured by Step (b1): A step of applying an alignment polymer to a substrate to form an alignment film layer. Step (b2): A composition containing a polymerizable liquid crystal compound represented by formula (A) is applied onto the alignment film layer. Cloth making process Step (b3): ​​A step of drying the applied composition and curing it by light irradiation.

[0091] The thickness of the optically anisotropic layer can be appropriately adjusted depending on the application, but is generally 0.1 μm to 10 μm. It is preferable that the thickness is 0.2 μm to 5 μm, and more preferable that the thickness is 0.2 μm to 5 μm in order to reduce the photoelasticity. It is nice.

[0092] Among these laminates, the polymerizable liquid crystal compounds were vertically aligned when viewed from an oblique angle on the light exit side. When a light source is used, linear polarization is converted to circular or elliptical polarization, and circular or elliptical polarization is converted to linear polarization. It is used as a retardation film to convert the direction of light emitted from a light source into a light having a different polarization direction, or to convert the direction of polarization of linearly polarized light. It is useful. The retardation film has excellent transparency in the visible light region and can be used as a member for various display devices. It can be used.

[0093] The laminate may be a laminate of a plurality of sheets, or may be combined with another film. A plurality of the present laminates having different orientation states of the crystal compounds are laminated, or the present laminate and another film are laminated. When combined with these, they can be used as viewing angle compensation films, viewing angle expansion films, anti-reflection films, and polarizing films. It can be used as a polarizing plate, a circular polarizing plate, an elliptically polarizing plate or a brightness enhancing film.

[0094] The optical properties of the laminate can be changed by adjusting the alignment state of the polymerizable liquid crystal compound. VA (vertical alignment) mode, IPS (in-plane switching) mode, OCB (op tically compensated bend) mode, TN (twisted nematic) mode, STN (super t Use as a retardation film for various liquid crystal display devices such as wisted nematic mode liquid crystal display devices. can be done.

[0095] When this laminate is used as a positive C plate, the front retardation value Re(550) is The thickness may be adjusted to a range of 0 to 10 nm, preferably 0 to 5 nm. Phase difference value R th is usually in the range of -10 to -300 nm, preferably -20 to -200 nm. The front retardation value Re(550) is adjusted to the range according to the characteristics of the liquid crystal cell. It is preferable to appropriately select the above-mentioned value, and the above-mentioned value is particularly suitable for compensation of an IPS mode liquid crystal display device.

[0096] Retardation value R in the thickness direction, which means the refractive index anisotropy in the thickness direction of the laminate th is the in-plane fast axis The phase difference value R is measured by tilting the axis by 50 degrees. 50 and the in-plane phase difference value R0 That is, the retardation value R in the thickness direction can be obtained. th is the in-plane phase difference value R0, and the fast axis is the inclination axis The phase difference value R measured at a 50 degree inclination 50 , the thickness d of the optically anisotropic layer, and the optically anisotropic From the average refractive index n0 of the conductive layer, n x , n y and n z Looking for, These can be substituted into equation (8) to perform the calculation.

[0097] R th =[(n x +n y ) / 2-n z ]×d (8) R0=(n x -n y )×d (9) R 50 =(n x -n y ')×d / cos(φ) (10) (n x +n y +n z ) / 3=n0(11) Where: φ=sin -1 [sin(50°) / n0] n y '=n y ×n z / 〔n y 2 ×sin 2 (φ)+n z 2 ×cos 2 (φ) 1 / 2

[0098] The optically anisotropic layer of the laminate of the present invention is transferred to a substrate via a pressure-sensitive adhesive. Thus, a second laminate consisting of the adhesive layer and the optically anisotropic layer can be obtained. The adhesive may be a known adhesive, and the transfer may be performed by a known method. The substrate to which the image is transferred may be the same as the substrate or polarizing plate. The second laminate of the present invention has the same optical properties as the laminate of the present invention. When the laminate of the present invention has a substrate, an alignment film layer, and an optically anisotropic layer, The optically anisotropic layer and the alignment film layer are transferred to a substrate via a pressure-sensitive adhesive. A second laminate consisting of an adhesive layer, an optically anisotropic layer and an alignment film layer can be obtained.

[0099] A schematic diagram of the present laminate is shown in Fig. 1. Fig. 1(a) shows a substrate 1 and an optically anisotropic layer 2 in this order. FIG. 1(b) shows a substrate 1, an alignment film layer 3, and an optically anisotropic The laminate 100 is made by laminating the conductive layer 2 and the conductive layer 3 in this order.

[0100] The laminate of the present invention is also useful as a member constituting a polarizing plate. and a polarizing film, and this laminate is usually included as a retardation film. Specific examples of the polarizing plate of the present invention include the polarizing plates shown in Figs. 2(a) to 2(d). The polarizing plate 110 shown in FIG. 2(a) comprises a polarizing film 4, an optically anisotropic layer 2, and a substrate. The polarizing plate 110 shown in FIG. 2(b) is a polarizing plate having a polarizing filter 1. The film 4, the substrate 1, and the optically anisotropic layer 2 are laminated in this order in the polarizing plate shown in FIG. The polarizing plate 110 to be formed comprises a polarizing film 4, an optically anisotropic layer 2, an alignment film layer 3, and a substrate 1. The polarizing plate 110 shown in FIG. 2(d) is a polarizing plate having a polarizing film 4, The polarizing plate is a laminate of a substrate 1, an alignment film layer 3, and an optically anisotropic layer 2 in this order. The film 4 and the optically anisotropic layer 2 or the substrate 1 may be bonded together using an adhesive and / or a pressure sensitive adhesive. stomach.

[0101] The polarizing film 4 may be any film having a polarizing function, for example, polyvinyl alcohol. A film made by adsorbing iodine or dichroic dye onto a coal-based film and stretching it, and a polyvinyl chloride film Examples include films in which iodine or dichroic dyes are adsorbed by stretching a vinyl alcohol-based film. can be done.

[0102] The polarizing film 4 may be protected with a protective film, if necessary. Examples of the polymers include polyolefins such as polyethylene, polypropylene, and norbornene-based polymers. Polyethylene terephthalate film, Polymethacrylate film , polyacrylic ester film, cellulose ester film, polyethylene naphtha Plate film, polycarbonate film, polysulfone film, polyethersulfone film Polyether ketone film, polyphenylene sulfide film and and polyphenylene oxide films.

[0103] The adhesive is preferably one that is highly transparent and has excellent heat resistance. Such adhesives include acrylic adhesives, epoxy adhesives, and urethane adhesives. Can be obtained.

[0104] The laminate can be used in various display devices. The display device is a device that displays a light and includes a light-emitting element or a light-emitting device as a light source. Display devices, organic electroluminescence (EL) display devices, inorganic electroluminescence EL display devices, touch panel display devices, electron emission display devices (e.g. field emission display devices) Field Emission Display (FED), Surface Field Emission Display (SED), Electronic Paper (Electronic Ink and Electric Display devices using electrophoretic elements, plasma display devices, projection type display devices (e.g. grating Light valve (GLV) display device, digital micromirror device (DMD) LCDs are transmissive displays and piezoelectric ceramic displays. type liquid crystal display device, semi-transmissive type liquid crystal display device, reflective type liquid crystal display device, direct-view type liquid crystal display device, This includes both projection-type liquid crystal display devices and projection-type liquid crystal display devices. These display devices are used to display two-dimensional images. In particular, the display device may be a display device that displays a three-dimensional image, or a stereoscopic display device that displays a three-dimensional image. The laminate is suitable for use in liquid crystal displays, touch panel displays, etc., depending on the axial relationship of the laminated optically anisotropic layers. Apparatus, organic electroluminescence (EL) display device and inorganic electroluminescence The present invention can be effectively used in electroluminescence (EL) display devices.

[0105] FIG. 3 is a schematic diagram of a liquid crystal display device including the present laminate. Examples of the liquid crystal display device include the liquid crystal display devices shown in Figs. 3(a) to 3(d). The liquid crystal display device shown in FIG. 3(a) to FIG. 3(d) is a liquid crystal panel having a polarizing plate 110 according to the present invention. A polarizing film 4' is attached to one side of the liquid crystal panel 5, and an adhesive and / or The polarizing film 4 has a structure in which the polarizing film 4 is bonded to the polarizing film 1 through an adhesive. The absorption axis of Room 4' is perpendicular.

[0106] This laminate suppresses light leakage during black display, especially in IPS (in-plane switching) mode. When used for compensation of an IPS mode display device, the slow axis of the substrate 1 and the polarizing filter The relationship between the absorption axis of the film 4 will now be described. In the configurations of FIG. 3(a) and FIG. 3(c), The absorption axis of the film 4 and the slow axis of the substrate 1 are parallel to each other. In the configurations of FIG. 3(b) and FIG. 3(d), If the absorption axis of the polarizing film 4 and the slow axis of the substrate 1 are perpendicular to each other, the anisotropy and optical anisotropy of the substrate Due to the anisotropy of the polarizing layer, when the polarized light emitted from the liquid crystal panel is viewed obliquely, In addition, the liquid crystal shown in FIG. 3(a) to FIG. 3(d) can be used to convert the light effectively. In the display device, a voltage is applied to the liquid crystal panel using electrodes (not shown). The liquid crystal orientation of the molecules changes, enabling a black and white display.

[0107] FIG. 4 is a schematic diagram of an organic EL display device including the present laminate. FIG. 4(a) shows a polarizing film 4, an optically anisotropic layer 2, a substrate 1 and an organic EL panel 6. FIG. 4(b) shows an organic EL display device in which the polarizing film 4, the substrate 1, and the The organic EL display device has an optically anisotropic layer 2 and an organic EL panel 6 laminated in this order. 4(c) is a polarizing film 4, an optically anisotropic layer 2, an alignment film layer 3, a substrate 1, and an organic EL panel. 4(d) shows an organic EL display device in which the polarizing film 4, the substrate 6, and the 1, an alignment film layer 3, an optically anisotropic layer 2, and an organic EL panel 6 are laminated in this order. In either case, the absorption axis of the polarizing film 4 and the slow axis of the substrate 1 are not aligned. If the laminate is laminated at a 45° angle, the laminate will function as a circular polarizer and will be suitable for use in an organic electroluminescence display. It can be used as an excellent anti-reflection layer for display devices. EXAMPLES

[0108] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" refer to the units "parts" and "parts". Unless otherwise specified, means mass % and mass part.

[0109] [Preparation of Oriented Polymer Composition] The composition of the oriented polymer composition is shown in Table 1. SE-610 (Nissan Chemical Industries, Ltd.) with N-methyl-2-pyrrolidone, 2-butoxy Ethanol and ethylcyclohexane were added to prepare an oriented polymer composition (A). Ta.

[0110] [Table 1] The values ​​in parentheses in Table 1 indicate the content ratio of each component relative to the total amount of the prepared composition. For SE-610, the solid content was calculated from the concentration listed on the delivery specifications.

[0111] Example 1 [Preparation of composition for forming optically anisotropic layer] The components in Table 2 were mixed and the mixture was stirred at 80° C. for 1 hour to obtain an optically anisotropic film. A composition 1 for forming a conductive layer was obtained.

[0112] [Table 2] The values ​​in parentheses in Table 2 indicate the content ratio of each component to the total amount of the prepared composition. . In Table 2, Irg369 is Irgacure (registered trademark) 36 manufactured by BASF Japan Ltd. 9, BYK361N is a leveling agent manufactured by BYK Japan, and Compound A 1 is a compound represented by the following formula: PGMEA is propylene glycol 1-monomer It is ethyl ether 2-acetate.

[0113] Compound A1: TIFF2024178356000019.tif30130

[0114] Compound A1 was synthesized by the method described in JP-A-2010-31223.

[0115] Example 1 [Laminate Production Example 1] Cycloolefin polymer film (substrate) (ZEONORFILM, Zeon Corporation) The surface of the plate was treated with a corona treatment device (AGF-B10, Kasuga Electric Co., Ltd.) at an output of 0 The treatment was performed once under conditions of 3.3 kW and a treatment speed of 3 m / min. An optically anisotropic layer is formed on the surface of the cycloolefin polymer film obtained by corona treatment. The composition for forming 1 was applied and dried, and then the composition for forming 1 was applied with Uni-Cure (VB-15201BY-A, USHIO Corporation). A 365 nm light beam was applied at 40 mW / cm under a nitrogen atmosphere using a microscope (manufactured by Epson Corporation). 2 Illuminance The resultant was irradiated with light at a temperature of 1000 V for 30 seconds to form an optically anisotropic layer 1, and a laminate 1 was obtained.

[0116] Example 2 [Laminate Production Example 2] Cycloolefin polymer film (substrate) (ZEONORFILM, Zeon Corporation) The surface of the plate was treated with a corona treatment device (AGF-B10, Kasuga Electric Co., Ltd.) at an output of 0 The treatment was performed once under conditions of 3.3 kW and a treatment speed of 3 m / min. The surface of the cycloolefin polymer film obtained by corona treatment is coated with an oriented polymer. The composition (A) was applied and dried to form an alignment film (1) having a thickness of 40 nm. The composition 1 for forming an optically anisotropic layer was applied to the surface of the alignment film (1) using a bar coater. The composition was heated to 0° C., dried, and cooled to room temperature. A vacuum was used (VB-15201BY-A, manufactured by Ushio Inc.) in a nitrogen atmosphere. 365 nm light at 40 mW / cm 2 The optically anisotropic layer 2 is formed by irradiating the layer with an illuminance of Thus, laminate 2 was obtained.

[0117] [Optical property measurements] The retardation values ​​of the optically anisotropic layers 1 and 2 were measured using a measuring instrument (KOBRA-WR, manufactured by Oji Scientific Instruments). First, the cycloolefin polymer film used as the substrate has no retardation. It was confirmed that there was no slow axis. The angle of incidence was changed and measurements were taken to confirm whether the liquid crystal was vertically aligned. The retardation value R(λ) was Phase difference value at an incident angle of 0 degrees (front), R 50 (λ) is the incidence angle of 50 degrees (inclination around the fast axis) The retardation values ​​were measured at a wavelength (λ) of 550 nm. The average refractive index n 0 is set to 1.60, and n x , n y and n z The results are shown in Tables 3 and 4. As shown in.

[0118] [Table 3]

[0119] [Table 4]

[0120] [Light leakage measurement] On both sides of the laminates 1 and 2 obtained in Examples 1 and 2, polarizing plates (iodine-based polarizing plates manufactured by Sumitomo Chemical Co., Ltd.) were attached. A polarizing plate (TRW842AP7) is usually attached to the substrate using adhesive so that the absorption axes of the polarizing plates are perpendicular to each other. The transmittance of the obtained laminate with the polarizing film at a wavelength of 550 nm was measured using an integrating sphere. The measurement was performed using a spectrophotometer (JASCO Corporation, V7100). Therefore, the substrate was placed on the polarizing plate (B) side, and light was incident from the polarizing plate (B) side. The results are shown in Table 5. As shown in.

[0121] [Table 5]

[0122] Example 3 [Laminate Production Example 3] The substrate used was a cycloolefin polymer film with a front retardation value of 120 nm. Except for the above, the same method as in Example 1 was used to form an optically anisotropic layer 3 having a thickness of 0.523 μm, and the laminate was then laminated. Got body 3.

[0123] Example 4 [Laminate Production Example 4] The substrate used was a cycloolefin polymer film with a front retardation value of 120 nm. Except for the above, the same method as in Example 2 was used to form an optically anisotropic layer 4 having a thickness of 0.514 μm, and the laminate was then laminated. Got body 4.

[0124] Example 5 [Laminate Production Example 5] The substrate used was PureAce WR (manufactured by Teijin Ltd.) with a front retardation value of 141 nm. An optically anisotropic layer 5 having a thickness of 0.550 μm was formed in the same manner as in Example 1, except that Laminate 5 was obtained.

[0125] Example 6 [Laminate Production Example 6] The substrate used was PureAce WR (manufactured by Teijin Ltd.) with a front retardation value of 141 nm. An optically anisotropic layer 6 having a thickness of 0.562 μm was formed in the same manner as in Example 2, except that Laminate 6 was obtained.

[0126] [Check for black display] A pressure-sensitive adhesive layer and a polarizing plate were attached to the optically anisotropic layer side of the laminates 3 to 6 produced in Examples 3 to 6. At this time, the transmission axis of the polarizing plate and the slow axis of the base material of the laminates 3 to 6 were approximately perpendicular to each other. The obtained laminate-attached polarizing plate was placed on an i-Pad from which the viewing-side polarizing plate had been removed. (registered trademark) (manufactured by Apple Inc.) on the visible side of the panel. The results are shown in Table 6.

[0127] [Table 6]

[0128] Example 7 [Laminate Production Example 7] Polyethylene terephthalate film (substrate) (Mitsubishi Plastics, Diafoil T The surface of the 140E25 was treated with a corona treatment device (AGF-B10, manufactured by Kasuga Denki Co., Ltd.). The corona treatment was performed once at a power output of 0.3 kW and a treatment speed of 3 m / min. The oriented polymer composition (A) is applied to the surface of the polyethylene terephthalate film. The resulting mixture was dried to form an alignment film (1) having a thickness of 40 nm. The substance 1 was applied to the surface of the alignment film (1) using a bar coater, heated to 120°C, dried, and The dried composition for forming an optically anisotropic layer was cooled to room temperature. A 365 nm light was applied for 40 h under a nitrogen atmosphere using a 365 nm light source (BY-A, manufactured by Ushio Inc.). mW / cm 2 The optically anisotropic layer 7 was formed by irradiating the layer with light at an illuminance of 100 nm for 30 seconds, and the laminate 7 was obtained. .

[0129] [Optical property measurements] The surface of the optically anisotropic layer 7 of the laminate 7 was treated with a corona treatment device at an output of 0.3 kW and a treatment speed of 1000 Hz. The corona-treated surface was then coated with cycloolefin resin via an adhesive. A thin polymer film (ZEONOR Film, manufactured by Zeon Corporation) was then laminated. The polyethylene terephthalate film and the orientation film were peeled off, and the cycloolefin polymer was A laminate 8 consisting of the film, the pressure-sensitive adhesive layer and the optically anisotropic layer 7 was obtained. The retardation value of the laminate 8 was measured using a measuring instrument (KOBRA-WR, manufactured by Oji Scientific Instruments). First, the cycloolefin polymer film used as the base material has no phase difference and no slow axis. It was confirmed that the incident angle of light to the sample having the optically anisotropic layers 1 and 2 laminated thereon was changed. The retardation value R(λ) was measured at an incidence angle of 0 degrees ( Phase difference value of the front 50 (λ) is the phase difference value at an incident angle of 50 degrees (inclination around the fast axis). The measurements were performed at a wavelength (λ) of 550 nm. The average refractive index n0 was 1.60 Then, from equations (9) to (11), n x , n y and n z The results are shown in Tables 7 and 8.

[0130] [Light leakage measurement] The surface of the optically anisotropic layer 7 of the laminate 7 obtained in Example 7 was subjected to output using a corona treatment device. The treatment was performed once under the conditions of 0.3 kW and a treatment speed of 3 m / min. A cycloolefin polymer film (having a front retardation value of 120 nm) was laminated thereon. Next, the polyethylene terephthalate film and the orientation film were peeled off, and the cycloolefin polyimide was A laminate 9 consisting of the polymer film, the pressure-sensitive adhesive layer and the optically anisotropic layer 7 was obtained. A polarizing plate was attached to the film using an adhesive so that the absorption axes of the polarizing plates were perpendicular to each other. The transmittance T of the laminate with optical film at a wavelength of 550 nm was measured using a spectrophotometer with an integrating sphere. The results are shown in Table 9.

[0131] [Check for black display] A pressure-sensitive adhesive layer and a polarizing plate were attached in this order to the surface of the optically anisotropic layer of the laminate 9 produced in Example 7. At this time, the polarizing plate was laminated so that the transmission axis of the polarizing plate and the slow axis of the base material of the laminate 9 were approximately perpendicular to each other. The obtained laminate-attached polarizing plate was attached to an i-Pad (registered trademark) from which the viewing-side polarizing plate had been removed. (Apple) on the viewing side, and the light leakage when black is displayed is measured in the direction of the panel surface. The results were visually confirmed from a 45° angle and an elevation angle of 45°.

[0132] [Table 7]

[0133] [Table 8]

[0134] [Table 9]

[0135] [Table 10]

[0136] It was confirmed that the laminate of the present invention is excellent in suppressing light leakage when viewed obliquely during black display. [Industrial Applicability]

[0137] The laminate of the present invention is an optical film excellent in suppressing light leakage when viewed obliquely during black display. It is useful. [Explanation of symbols]

[0138] 1: Base material 2: Optically anisotropic layer 3: Alignment layer 4, 4': Polarizing film 5: LCD panel 6: Organic EL panel 100: This laminate 110: Polarizing plate

Claims

1. The present invention has a substrate and an optically anisotropic layer, and the optically anisotropic layer is represented by the following formulas (1), (2) and (3): a coating layer obtained from a composition containing a polymerizable liquid crystal compound, a photopolymerization initiator, and a leveling agent, the polymerizable liquid crystal compound being a compound represented by formula (A), [In formula (A), X 1 is an oxygen atom, a sulfur atom, or -NR 1 - represents. 1 is a hydrogen atom or a group having 1 to 4 carbon atoms represents an alkyl group represented by the formula: Y 1 represents a monovalent aromatic hydrocarbon group having 6 to 12 carbon atoms which may have a substituent, or It represents a monovalent aromatic heterocyclic group having 3 to 12 carbon atoms which may have one or more groups. Q 3 and Q. 4 each independently represents a hydrogen atom or a C1 to C20 a monovalent aliphatic hydrocarbon group, an alicyclic hydrocarbon group having 3 to 20 carbon atoms, or A monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a halogen atom, a cyano group, a nitro group, N.R. 2 R 3 Or -SR 2 represents or Q 3 and Q. 4 are bonded to each other, and each of these is bonded R2 and R3 may form an aromatic ring or an aromatic heterocyclic ring together with the carbon atom to which they are bonded. , each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. D 1 and D. 2 each independently represents a single bond, —C(═O)—O—, —C(═S)—O—, -CR 4 R 5 -、-CR 4 R 5 -CR 6 R 7 -、-O-CR 4 R 5 -、-CR 4 R 5 -O -CR 6 R 7 -、-CO-O-CR 4 R 5 -、-O-CO-CR 4 R 5 -、-CR 4 R 5 -O-CO-CR 6 R 7 -, -CR 4 R 5 -CO-O-CR 6 R 7 -or-NR 4 -CR 5 R 6 -or-CO-NR 4 Represents -. R 4 , R 5 , R 6 and R 7 each independently represents a hydrogen atom, a fluorine atom, or a group having 1 to 4 carbon atoms represents an alkyl group represented by the formula: G 1 and G 2 each independently represents a divalent alicyclic hydrocarbon group having 5 to 8 carbon atoms, The methylene groups constituting the cyclic hydrocarbon group are replaced by oxygen atoms, sulfur atoms, or -NH-. The methine group constituting the alicyclic hydrocarbon group may be replaced with a tertiary nitrogen atom. This is also fine. L 1 and L 2 each independently represents a monovalent organic group; L 1 and L 2 At least One of the groups is an organic group having a polymerizable group. The leveling agent is a polyacrylate-based leveling agent and a perfluoroalkyl-based The leveling agent is selected from the group consisting of the leveling agents listed above. Δn 50 (450) / Δn 50 (550)≦1.00 (1) 1.000≦Δn 50 (950) / Δn 50 (55) (2) (where Δn 50 (450), Δn 50 (550), Δn 50 (650) is a wave At wavelengths of 450 nm, 550 nm, and 650 nm, the fast axis is inclined by 50 degrees. The birefringence is derived from the retardation value obtained when the film is subjected to the measurement.) nz>nx≒ny (3) (nx and ny indicate the refractive index in the direction parallel to the substrate plane, and nx and ny are respectively nz indicates the refractive index in a direction perpendicular to both nx and ny.)

2. 2. The laminate according to claim 1, which has an alignment film layer between the substrate and the optically anisotropic layer, the alignment film layer comprising at least one member selected from the group consisting of polyimide, polyamide and polyamic acid.

3. 3. The stacked structure according to claim 2, wherein the alignment film layer has an alignment control force for vertically aligning the polymerizable liquid crystal compound. Layered body.

4. A polarizing plate (A), the laminate according to any one of claims 1 to 3, and a polarizing plate (B) laminated in this order. In the structure, the absorption axes of the polarizing plate (A) and the polarizing plate (B) are perpendicular to each other, and the following (a) and (b) are satisfied: In either case, light is incident from the polarizing plate (B) side and transmitted from the polarizing plate (A) side. The transmittance T at a wavelength of 550 nm obtained when detecting light satisfies the following formula (D): The laminate according to any one of claims 1 to 3. (a) When the slow axis exists in the plane of the substrate constituting the laminate, the substrate is disposed on the polarizing plate (B) side. The substrate is disposed so that the slow axis of the substrate is parallel to the absorption axis of the polarizing plate (B). (b) When the slow axis does not exist within the plane of the substrate constituting the laminate, the substrate is disposed on the polarizing plate (B) side. Place. 0.000<T<0.005 (D) (Here, the transmittance T is the transmittance when the absorption axes of the polarizing plate (A) and the polarizing plate (B) are arranged parallel to each other.) (This is the value when the pass rate is 100%)

5. The laminate according to any one of claims 1 to 4, wherein the substrate satisfies the following formula (4): nx>ny≒nz (4) (where nx and ny indicate the refractive indices in the direction parallel to the substrate plane, nz indicates the refractive index in a direction perpendicular to both nx and ny.)

6. The laminate according to any one of claims 1 to 5, wherein the substrate satisfies the following formulas (5) and (6): Δn(450) / Δn(550)≧1.00 (5) 1.00≧Δn(650) / Δn(550) (6) (Δn(450), Δn(550), and Δn(650) are wavelengths of 450 nm and 550 nm, respectively. The birefringence is derived from the front retardation value when measured at 650 nm and 650 nm. )

7. The laminate according to any one of claims 1 to 6, wherein the substrate satisfies the following formulas (7) and (8). Δn(450) / Δn(550)≦1.00 (7) 1.00≦Δn(650) / Δn(550) (8) (Δn(450), Δn(550), and Δn(650) have the same meanings as above.)

8. A polarizing plate comprising the laminate according to any one of claims 1 to 7.

9. A display device comprising the laminate according to any one of claims 1 to 8.

10. The optically anisotropic layer in the laminate according to any one of claims 1 to 4 is bonded to the laminate via a pressure-sensitive adhesive. The second laminate including the substrate, the adhesive layer, and the optically anisotropic layer is formed. The method for producing the laminate is as follows:

Citation Information

Patent Citations

  • Cyclic ether polymerizable liquid crystal composition, homeotropically aligned liquid crystal film and method for producing homeotropically aligned liquid crystal film

    JP2006342332A

  • Homeotropic alignment liquid crystal film requiring no alignment film and method for producing same

    JP2008523443A

  • Liquid crystal film and liquid crystal display element mounting optical film composed of the liquid crystal film

    JP2009249482A

  • Brightness-enhanced film, method for forming the same, and liquid crystal display device

    JP2011118137A

  • Composite retardation plate and method for producing the same

    JP2011150314A